Boosting Bismuth(III) Complexation for Targeted α‐Therapy (TAT) Applications with the Mesocyclic Chelating Agent AAZTA. Issue 43 (29th September 2022) - Horváth, Dávid; Vágner, Adrienn; Szikra, Dezsö; Trencsényi, György; Demitri, Nicola; Guidolin, Nicol; Maiocchi, Alessandro; Ghiani, Simona; Travagin, Fabio; Giovenzana, Giovanni B.; Baranyai, Zsolt
Abstract: Targeted α therapy (TAT) is a promising tool in the therapy of cancer. The radionuclide 213 Bi III shows favourable physical properties for this application, but the fast and stable chelation of this metal ion remains challenging. Herein, we demonstrate that the mesocyclic chelator AAZTA quickly coordinates Bi III at room temperature, leading to a robust complex. A comprehensive study of the structural, thermodynamic and kinetic properties of [Bi(AAZTA)] − is reported, along with bifunctional [Bi(AAZTA‐C4‐COO − )] 2− and the targeted agent [Bi(AAZTA‐C4‐TATE)] −, which incorporates the SSR agonist Tyr 3 ‐octreotate. An unexpected increase in the stability and kinetic inertness of the metal chelate was observed for the bifunctional derivative and was maintained for the peptide conjugate. A cyclotron‐produced 205/206 Bi mixture was used as a model of 213 Bi in labelling, stability, and biodistribution experiments, allowing the efficiency of [ 213 Bi(AAZTA‐C4‐TATE)] − to be estimated. High accumulation in AR42J tumours and reduced kidney uptake were observed with respect to the macrocyclic chelate [ 213 Bi(DOTA‐TATE)] − . Abstract : [Bi(AAZTA)] − and derivatives have been comprehensively characterized. Fast formation, remarkable stability, and strong accumulation in AR42J tumour make 213 Bi(AAZTA‐C4‐TATE)] − an outstanding candidate for TAT.